Correlation of clinical examination and ultrasonogram with histopathology in predicting the metastatic axillary lymph nodes in breast cancer - Rony, Jacob; Krishnakumar, Marar; Babu, Moothedathparambil Ramakrishnan (International Surgery Journal, 2016)
Background: Examination of breast and axilla is an integral part of triple assessment of patient with suspected carcinoma breast. A retrospective study was conducted to compare the axillary lymph nodes in carcinoma breast based on clinical, ultrasonogram (USG) and post-operative histopathology (HPR). Methods: One hundred patients with early breast cancer were included in the study. Clinical examination of axilla, followed by USG examination of all patients was done preoperatively. This was compared with the post-operative HPR of axillary lymph nodes (gold standard). The validity of the findings was evaluated by using sensitivity and specificity. Results: There is a strong positive correlation for the detection of total number of lymph nodes (r=0.935) between USG and HPR which is statistically significant (p <0.05). The correlation between clinical detection and HPR detection of axillary lymph nodes was weak (r= 0.278). Accuracy of the USG findings was good (81%) compared to the HPR findings and this was statistically significant (p <0.05). The USG morphologic lymph node features with the greatest correlation with malignancy were loss of central fatty hilum (r= 0.953) and cortical thickness (r= 0.914). In HPR and USG, the number of positive lymph nodes was high in stage II. Conclusions: The sensitivity for detecting malignancy by USG is only average. USG is more likely to detect an abnormal node if there is morphologic features of increased cortical thickening and loss of central fatty hilum. A multidisciplinary effort is needed to reduce unnecessary axillary dissections.